Knowledge and awareness of HIV self-testing among Australian gay and bisexual men: a comparison of never, sub-optimal and optimal testers willingness to use. Issue 2 (1st February 2019) - Dean, Judith; Lui, ChiWai; Mutch, Allyson; Scott, Michael; Howard, Chris; Lemoire, Jime; Crothers, Anna; Fitzgerald, Lisa; Williams, Owain D.
ABSTRACT: This paper explores the willingness to use and pay for HIV Self-testing (HIVST) among Australian gay and bisexual men (GBM). Bivariate and univariate multinominal logistic regression of data from an online survey was performed. Thirty-one (13%) had never HIV tested and 41.9% (88) were testing sub-optimally by Australian guidelines. Half (58.4%, 136) had never heard of HIVST, however, 56.2% (131) reported willingness to use HIVST, with sub-optimal (OR=2.13; p  < 0.01) and never-testers (OR=2.01; p  < 0.10) significantly more likely to do so than optimal-testers. Most were confident (51.7%, 119) or somewhat confident (29.1%, 67) accessing support following a reactive result, however, never-testers were significantly less confident compared to previous testers (OR=3.47; p < 0.05). Less than a quarter (23.6%, 57) were willing to pay for a kit with AUD$15 ( R 2 = 0.9882) the estimated preferred price. This research confirms that HIVST is an important and accepted adjunct to established HIV testing modalities, particularly among sub-optimal and never-testers and that online (61.6%, 143) or clinic-based (61.6%, 143) dissemination are preferred. Research examining how best to disseminate HIVST in a range of safe and effective models needs to continue to ensure HIVST is part of a comprehensive strategy that facilitates usage and linkages to care.